An engonomic design on the manual handling and palletizing task at Pepsi Cola products Philippines, Inc. - Alejandrino, Michael James J. (Animo Repository, 1999)
The working body postures of the laborers are dependent on the design of the workstation. The productivity of the workers is based on how well they perform their tasks. This study is conducted to improve the manual palletizing of heavy loads. This is based on the workstation and task design of the manual palletizing of heavy loads. This is based on the workstation and task design of the manual palletizers of the filled one-liter bottle line tested the proposed lowering mechanism assembly. With the use of the different tools and techniques in the assessment of the working postures assumed and loads lifted by the workers, the use of the proposed design showed significant improvements regarding the postures and the tasks that correspond to the workstation design. The management would be the benefactor of the study because it is one of the gauges of productivity. The study would contribute to minimize the total man hours lost due to the problems experienced by the workers. A make shift palletizing workstation was made. The major component of the assembly is the lowering mechanism, which is designed to promote better working movements of the worker. The worker would not adjust to the level of the piles of softdrink cases anymore when palletizing. The platform and conveyor are also adjusted in such a way that the palletizer would only have one type of movement when performing the level stacking of cases. The material used in the lowering mechanism is steel so that it could stand the heavy load to be placed on it, which is a pallet of four levels of filled one-liter softdrink cases. The results of the study showed that the design objectives were achieved. The extreme trunk bending and twisting were minimized. The long lift distances traveled were reduced. Accordingly, the force acting on the L5/S1 disc is also reduced.